2017
DOI: 10.1155/2017/7198645
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Meets Biological Networks of Complex Diseases: A Computational Perspective

Abstract: With the rapid development of cheminformatics, computational biology, and systems biology, great progress has been made recently in the computational research of Chinese herbal medicine with in-depth understanding towards pharmacognosy. This paper summarized these studies in the aspects of computational methods, traditional Chinese medicine (TCM) compound databases, and TCM network pharmacology. Furthermore, we chose arachidonic acid metabolic network as a case study to demonstrate the regulatory function of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…With computational chemistry and biology becoming a cutting-edge technology in biomedical research, many studies have demonstrated its power in the field of herbal medicine as well [ 6 ]. Such approaches offer us not only rapid and accurate predictions but also, and more importantly, a comprehensive understanding at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…With computational chemistry and biology becoming a cutting-edge technology in biomedical research, many studies have demonstrated its power in the field of herbal medicine as well [ 6 ]. Such approaches offer us not only rapid and accurate predictions but also, and more importantly, a comprehensive understanding at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies on TCMs have in many ways enabled researchers to better understand the synergistic mechanism of the herbs at the molecular and network levels prior to laboratory investigation and clinical use. 67,68 Although such techniques have yet to be applied to LB, research using various multi-component LB extracts is ongoing. Synergism with other drugs, such as paclitaxel/ cisplatin in the treatment of ovarian cancer, 69 interferon-α2b in renal cell carcinoma, 70 and others, has also been observed.…”
Section: Composition: Single Component Versus Synergistic Blends In Rmentioning
confidence: 99%
“…It was originated from the first literature of Shennong's Materia Medica (~220 CE). Herbal medicine is an important treasure of Chinese nation, which has been used for thousands of years and gained remarkable effects on the treatment of various diseases including tumor, due to accumulating abundant theoretical and practical knowledge through thousands of years [ 8 ], and the abundant herb resource has also provided essential material foundation to look for new anticancer drugs [ 9 11 ]. The modern success of using taxol and artemisinin further proves its value.…”
Section: Introductionmentioning
confidence: 99%